FISCAL POLICY OTONOMI DAERAH (Kajian Penerimaan Fiscal Decentralization Di Provinsi Riau) - Muhammad Aras (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
The implementation of regional autonomy in Indonesia is manifested in the form of delegation or handover of central government authority to regional governments, approved in Law Number 22 of 1999 which has been amended by UU Number 32 of 2003, concerning regional government. In the request for fiscal decentralization, it has been enacted since January 1, 2001, applied pursuant to UU Number 25 of 1999, concerning financial balance between the central government and regional governments. However, the aforementioned Law (UU No. 25/1999 and UU No.22 / 1999) does not regulate the distribution of duties on the provision of public goods (public services), for example, in the education and health sector, so that it can be announced about the spending authority allocated to the regions by the central government is delegated authority. Because it applies the principle of